2021
DOI: 10.1186/s12872-021-02285-y
|View full text |Cite
|
Sign up to set email alerts
|

Difference in left atrial D-dimer level in patients with atrial fibrillation treated with direct oral anticoagulant

Abstract: Background Atrial fibrillation (AF) may cause cerebral and systemic embolism. An increased D-dimer level indicates hyperactivation of secondary fibrinolysis, resulting in predilection for thrombosis. To clarify the differential effects of anticoagulation therapy, we compared the D-dimer levels in peripheral and left atrial (LA) blood of atrial fibrillation patients scheduled for ablation. Methods We analyzed 141 patients with non-valvular AF (dabig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Tests involving D-dimer, prothrombin fragment F1 + 2, and left-ventricular ejection fraction (LVEF) can be useful in verifying hypercoagulability in patients with AF who are undergoing DOAC treatment. The results indicate that the effectiveness of apixaban as an anticoagulant might be superior to that of edoxaban in patients with NVAF, as demonstrated by lower levels of left-atrial D-dimer in the apixaban group, compared to the edoxaban group [78].…”
Section: D-dimermentioning
confidence: 86%
“…Tests involving D-dimer, prothrombin fragment F1 + 2, and left-ventricular ejection fraction (LVEF) can be useful in verifying hypercoagulability in patients with AF who are undergoing DOAC treatment. The results indicate that the effectiveness of apixaban as an anticoagulant might be superior to that of edoxaban in patients with NVAF, as demonstrated by lower levels of left-atrial D-dimer in the apixaban group, compared to the edoxaban group [78].…”
Section: D-dimermentioning
confidence: 86%
“…F1 + 2 is a peptide liberated from prothrombin when it is converted to thrombin by activated factor X (FXa). It re ects thrombin production and is a coagulation activation marker [22,23]. A previous study of patients administered DOAC therapy revealed that inappropriate underdosing was a risk factor for recurrent ischemic stroke [24].…”
Section: Discussionmentioning
confidence: 99%